Development and Validation of an HPLC-MS/MS Method for Quantification of Apixaban in Human Plasma - U. D. Filonova; P. K. Karnakova; K. K. Karnakova; M. O. Popova; A. A. Popova; O. A. Archakova; T. N. Komarov; I. E. Shohin (Разработка и регистрация лекарственных средств, 2024)
Introduction. Apixaban is an anticoagulant used in a number of thromboembolic diseases with an improved benefit-to-risk ratio, according to multiple clinical studies. Due to the prescription of apixaban as antithrombotic therapy in patients with COVID-19, an increase in its use has been observed. Thus, due to the widespread use of apixaban and the need to conduct pharmacokinetic and bioequivalence studies of the drug, it is important to develop and validate a simple and sensitive method for the quantitative determination of apixaban in human blood plasma.Aim. The aim of the study is to develop and validate a method for the determination of apixaban in human blood plasma using high-performance liquid chromatography with tandem mass selective detection (HPLC-MS/MS) for the subsequent bioanalytical study.Materials and methods. The determination of apixaban in human plasma was carried out by HPLC-MS/MS with rivaroxaban as an internal standard. The method of protein precipitation with acetonitrile was used as sample preparation. Mobile phase: 0.1 % solution of formic acid in water (eluent A); 0.1 % solution of formic acid in acetonitrile (eluent B). The total run time was 3.00 min. Column: Shim-pack Velox Biphenyl; 2.7 µm; 50 × 2.1 mm. Ionization source: electrospray with positive ionization mode. MRM transitions: 460.15 → 443.10 m/z (apixaban); 436.05 → 144.95 m/z (rivaroxaban).Results and discussion. The developed method was validated in accordance with the EAEU requirements for the following parameters: selectivity, calibration curve, accuracy and precision, lower limit of quantitation, suitability of standard samples, matrix effect, recovery, stability, carry-over, dilution effects. The parameters met the acceptance criteria.Conclusion. The confirmed analytical range of the developed and validated method was 1.00–300.00 ng/mL in blood plasma. The method for determining apixaban in blood plasma is simple and sensitive. This method was tested during the analytical part of the bioanalytical study and can be used to conduct other pharmacokinetic studies of apixaban drugs.